2020
DOI: 10.18502/ssu.v27i11.2494
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alcoholic Extract of Scrophularia Striata on Improving Spatial Memory in the Model of Crystal Meth Addiction in Male Rats

Abstract: Introduction: Crystal meth by induction of free radical formation in brains cells and lipid peroxidation cause to the apoptosis. The aim of present study is to investigate the effect of extract of Scrophularia striataon spatial memory, lipid peroxidation and alteration of antioxidant enzymes levels. Methods: In this experimental study, 42 male Wistar rats were divided into 6 groups, including: sham (saline), crystal meth (10, 15 mg/kg), Scrophularia Striate extract (200 mg/kg) and pretreatment of Scrophu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Purushothuman et al showed the neuroprotective effects of saffron on dopaminergic HeLa cells in rats and confirmed the relationship between the interactions of dopaminergic and cholinergic systems [ 60 ]. Hatami et al investigated the improvement of spatial memory by saffron extract in Parkinsonian rats and showed that pretreatment with saffron extract in PD rats led to a significant improvement in spatial memory [ 61 ]. Pan et al demonstrated the protective effects of saffron on primary dopaminergic cells against cell death by promoting cytoprotective responses to oxidative stress through the increased expression of nuclear factor erythroid 2–related factor 2 (Nrf2), as a regulator of cellular resistance to oxidants, in rotenone-induced PD models [ 62 ].…”
Section: Pre-clinical Studiesmentioning
confidence: 99%
“…Purushothuman et al showed the neuroprotective effects of saffron on dopaminergic HeLa cells in rats and confirmed the relationship between the interactions of dopaminergic and cholinergic systems [ 60 ]. Hatami et al investigated the improvement of spatial memory by saffron extract in Parkinsonian rats and showed that pretreatment with saffron extract in PD rats led to a significant improvement in spatial memory [ 61 ]. Pan et al demonstrated the protective effects of saffron on primary dopaminergic cells against cell death by promoting cytoprotective responses to oxidative stress through the increased expression of nuclear factor erythroid 2–related factor 2 (Nrf2), as a regulator of cellular resistance to oxidants, in rotenone-induced PD models [ 62 ].…”
Section: Pre-clinical Studiesmentioning
confidence: 99%
“…Experiments demonstrated neuroprotective effects of crocin in PD-induced mouse models by decreasing oxidative stress [ 83 ]. In PD rat models, improved spatial memory was observed upon treatment with saffron extracts [ 141 ]. The saffron extracts were reported to enhance the cellular expression of nuclear factor erythroid 2–related factor 2 (Nrf2), mediating resistance to oxidative stress in rotenone-induced PD models [ 142 ].…”
Section: Role Of Saffron Bioactive Compounds Against Human Diseasesmentioning
confidence: 99%